Los crustáceos decápodos Brachyura del litoral bonaerense (R.Argentina) - Boschi, Enrique E. (1964)
In this work the taxonomy of the Brachyura Decapod Crustacea from fthe shelfwaters of the Province of Buenos Aires, Argentina (South Atlantic Ocean) is described, with particular reference to the biology and zoogeography. The material and methods are described and various zoogeographical problems are considered. A total of 25 species were encountered, and each one is briefly described together with its ecological and biological data. In many cases the geographical distribution has been extgended. Keys are given for the identification of the more common Brachyura from Argentina, as also for the sub-divisions of the Brachyura, including ffamilies, subfamilies and genera. The so-called "cangrejal" community (community composed of semiaquatic crabs) of the river Salado was studied, which was composed of Chasmagnathus granulata crabs. The species Uca uruguayensis formed the outer limit of the "cangrejal" community.